Doppler Assessment of Uterine and Intraovarian Blood Flow in Patients with Genital Endometriosis - V. D. Vorobii (Zaporožskij Medicinskij Žurnal)
The spread of endometriosis among women of reproductive age is 5–10 %. Forming of endometrioid foci commonly begins from development of new blood vessels. So, changes of hemodynamics in vessels that can be determined by Doppler are important for complete diagnosis of endometriosis.